Diversity, Abundance, and Distribution Patterns of Natural Enemy Insects on Chili (Capsicum annum L.) in Bincau Village, Banjar Regency, South Kalimantan - Manap Trianto; Fajri Marisa; Moh Dahri Kisman (Universitas Islam Negeri Mataram, 2020)
Chili is a widely cultivated plant by the community because of its profit. Currently, in maintaining the quality of chili, people commonly use a lot of pesticides. In contrast, naturally, there are biological agents in the shape of natural enemy insects, more effective, and environmentally friendly. This study aims to determine the diversity, abundance, and distribution patterns of natural enemy insects in chili plantation (Capsicum annum L.) at Bincau Village, Martapura District, Banjar Regency, South Kalimantan. The sample is collected by pitfall trap, yellow pan trap, and sweep net method. Obtained data are analyzed by Shannon Wienner index (H'), Meyer abundance index, Morisita index (Id), and PCA method for environmental parameter analysis. The results showed the diversity of natural enemy insects on chili plants was moderate (H' = 2.396). Furthermore, the highest abundance in research is demonstrated on Hymenoptera order, which consisted of 9 families, 16 species, and 1,009 individuals. The distribution pattern of natural enemy insects in chili plantations is clustered (Id > 1). Based on the PCA analysis method, the temperature has the most impact on natural enemy insects' presence in this study.